2016
DOI: 10.13073/fpj-d-15-00063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Combustion Parameters of Impregnated and Varnished Cedar Wood (Cedrus libani)

Abstract: The present study investigated the effect of various types of impregnating and surface treatment materials on the fire resistance of wood material indoors and outdoors. Wood samples (Cedrus libani A. Rich.) were impregnated with Wolmanit-CB or Tanalith-E according to ASTM D1413‐76 (American Society for Testing and Materials 1976). The impregnated surface was treated with either synthetic or water-based outdoor varnish materials. The impregnated and varnished samples were left in outdoor conditions for 1 year. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In future studies; wood preservatives can be tested on samples in different sizes by applying different concentrations and pressures. The varnish types reduced the total time of combustion between 19-21% and raised the demolition time between 10-22% [3][4][5][6]38]. Wolmanit-CB raised the average temperature values in combustion with flame and combustion without flame, kept the minimum combustion temperatures high.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In future studies; wood preservatives can be tested on samples in different sizes by applying different concentrations and pressures. The varnish types reduced the total time of combustion between 19-21% and raised the demolition time between 10-22% [3][4][5][6]38]. Wolmanit-CB raised the average temperature values in combustion with flame and combustion without flame, kept the minimum combustion temperatures high.…”
Section: Resultsmentioning
confidence: 99%
“…The compression strength values were decrease with tanalith-E to control samples [2]. There are many ongoing researches to increase the resistance of wood especially against combustion and the environmental factors in the wood's place of use [3][4][5][6]. Water-based solutions prepared from water-borne salt like oil-based creosote, petrol solution *Sorumlu Yazar (Corresponding Author) e-posta : ssyasar@gumushane.edu.tr pentachlorophenol and CCA, ACQ, CCB, CCP and CBA are commonly used wood preservatives [7].…”
Section: Introductionmentioning
confidence: 99%
“…As a results of study boron compounds showed a decreasing impact on combustion properties of the laminated wood materials. In a similar study Fidan et al [8] investigated the effect of impregnation materials and synthetic or water-based varnish on the combustion properties of wood (Cedrus libani A. Rich.)…”
Section: Introductionmentioning
confidence: 99%